KEPENTINGAN PERTAHANAN KOREA SELATAN MELALUI JOINT TEAM KOREA DALAM WINTER OLYMPIC 2018 - Lokanata Putra S, A.A. Gede Oka; Sushanti, Sukma; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research describes the national interests that South Korea attempts to achieve in the form of security through the 2018 Winter Olympic Games as a tool to establish diplomatic relations with North Korea. Security issues on the Korean Peninsula are caused by provocative actions carried out by North Korea by carrying out a series of tests and development of nuclear weapons which are troubling not only South Korea but also the international community. For this reason, South Korea, through President Moon Jae-In, seeks to establish diplomatic relations with North Korea through the 2018 Winter Olympic Games to pursue security on the Korean Peninsula by initiating cooperation, dialogues and meetings in order to realize peace and prosperity on the Korean Peninsula. To make this effort a success, South Korea is supported and assisted by the United States as an alliance in dealing with North Korea's nuclear issue and the international community. Keywords: South Korea, North Korea, Nuclear, Winter Olympic , Defense